Pengaruh Fluktuasi Harga Emas dan Kurs Terhadap Return on Assets (ROA) Bank Syariah Indonesia Tahun 2018-2025 - Dela Puspita Sari; Eka Sri Wahyuni; Katra Pramadeka (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of gold price fluctuations and exchange rates on the Return on Assets (ROA) of Bank Syariah Indonesia during the 2018–2025 period. Profitability, as measured by ROA, is an important indicator for assessing a bank’s ability to manage its assets efficiently to generate profits. Gold price fluctuations and exchange rate movements are considered external factors that may affect the profitability of Bank Syariah Indonesia because they are closely related to economic conditions and the bank’s financing activities. This study employed a quantitative approach using an associative research design. The data used were secondary data obtained from the financial statements of Bank Syariah Indonesia, gold price data, and the Indonesian rupiah exchange rate against the United States dollar for the 2018–2025 period, presented on a quarterly basis, resulting in 32 observations. The sampling technique used was saturated sampling. Data were analyzed using multiple linear regression with the assistance of EViews software. The results showed that, partially, gold price fluctuations had a significant effect on Return on Assets (ROA) with a significance value of 0.001 < 0.05. The exchange rate also had a significant effect on ROA with a significance value of 0.002 < 0.05. Simultaneously, gold price fluctuations and exchange rates had a significant effect on the Return on Assets (ROA) of Bank Syariah Indonesia with a significance value of 0.002 < 0.05. Therefore, gold price fluctuations and exchange rates are factors that influence the profitability of Bank Syariah Indonesia during the study period.